Dr. Ambedkar’s as a writer and Thinker: His Vision and patriotism - Dr. Kuldeep Singh (Innovative Research Thoughts, 2023)
Theodore Roosevelt, Winston Churchill, John F. Kennedy, Martin Luther King Jr., Nelson Mandela and Dr. Ambedkar are the names which belong to different times as well as the different parts of the world. But they have one thing in common, i.e. they all delivered powerful and epoch making speeches which shaped the history of races and nations. Ambedkar’s final speech in Constituent Assembly which was delivered on November 25, 1949 can easily be termed as one of the greatest speeches ever delivered not only in India but also in the known history of entire mankind. Dr. Ambedkar, who is viewed as a national hero today and whom any political party can ignore only at its own peril, faced much social and political hostility during his life time. He did not allow the discrimination and insult he had to deal with during his formative years to fill him with bitterness and negativity. On the other hand, he made full use of the opportunities that came his way in a positive and constructive manner and rose to great heights as a scholar. So much so that out of the 389 members of Constituent Assembly, Ambedkar was the person who was considered to be scholarly and equipped enough to be the Chairman of the Draft Committee. On November 25, 1949, Ambedkar delivered the speech which revealed to the posterities the thinker, philosopher, visionary, reformer, rationalist, logician, humanist and nationalist that he was.